Thermal enhancement of plastering mortars with phase change materials : experimental and numerical approach - Sá, Ana Vaz (2012)
Building materials with incorporated Phase Change Materials (PCM) are meant to increase heat storage capacity, enable stabilization of interior surface temperatures of buildings whereby influencing the thermal comfort sensation and the stabilization of the interior ambient temperatures. This paper presents the development and characterization of a new composite construction material that consists in embedding micro-encapsulated PCM in plastering mortar. This research work also aimed experimental and numerical investigation of the first application of the new composite material with the goal of highlighting behavioural differences in regard to common mortars. For that propose two small-scale test cells were built: one with recourse to conventional mortar; and other with PCM plastering mortar. Both cells were monitored when subjected to realistic temperature cycles, with high temperature variation, in order to assess the effect of PCM incorporation. The numerical modelling of the experiments allowed a better understanding of the phenomena involved, and validation of the simulation tool. Based on such simulation tool, parametric analyses have been conducted in view of alterative PCM characteristics and concentrations.